2015
DOI: 10.1186/s12985-015-0406-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasonography for the diagnosis of 11 patients with acute respiratory distress syndrome due to bird flu H7N9 infection

Abstract: BackgroundA novel reassortant avian-origin influenza A (H7N9) virus was found to infect three Chinese residents, the first H7N9 infection in humans in Asia. Chest computed tomography (CT) for acute respiratory distress syndrome (ARDS) diagnosis is not only expensive but also exposes patients to radiation and might cause patients to be at risk of infection during transportation; in addition, chest radiography cannot be used to monitor the lung repeatedly in real time. Therefore, the routine use of bedside lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 25 publications
(18 reference statements)
3
31
0
1
Order By: Relevance
“…Literature suggests that lung ultrasonography (LUS) can have diagnostic accuracy better than CXR and comparable to CT scan in diagnosing lung pathologies (3,(5)(6)(7)(8)(9). Ultrasonography (USG) was conventionally performed by radiologists, but is now gaining popularity amongst intensivists as it can help in early diagnosis and quick therapeutic decision-making because of its easy bedside availability (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature suggests that lung ultrasonography (LUS) can have diagnostic accuracy better than CXR and comparable to CT scan in diagnosing lung pathologies (3,(5)(6)(7)(8)(9). Ultrasonography (USG) was conventionally performed by radiologists, but is now gaining popularity amongst intensivists as it can help in early diagnosis and quick therapeutic decision-making because of its easy bedside availability (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography (USG) was conventionally performed by radiologists, but is now gaining popularity amongst intensivists as it can help in early diagnosis and quick therapeutic decision-making because of its easy bedside availability (10,11). Most of the studies in the literature have targeted individual lung pathologies (3,6,8,9), but those comprehensively evaluating diagnostic accuracy of point of care LUS in detecting all lung pathologies together in comparison with CXR and CT scan are limited (4).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that bedside ultrasound can be used to evaluate H7N9 avian influenza infection in patients with ARDS, providing a strong basis for adjusting the treatment plan for patients. Therefore, LUS could be useful for the timely monitoring of ARDS caused by the H7N9 virus in clinics,[ 23 ] especially in resource-scarce settings or situations such as future respiratory virus outbreaks or pandemics. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, LUS is unable to distinguish early COVID-19 from other viral pneumonitis such as RSV, H1N1 20 or H7N9. 21 In the coming months, if the pendulum swings away from COVID-19 and towards alternate causes of respiratory failure, a rethink of the diagnostic approach of COVID-19 using LUS will be necessary.…”
Section: Limitations To Using Lus For Covid-19mentioning
confidence: 99%